2015
DOI: 10.1016/j.athoracsur.2015.04.135
|View full text |Cite
|
Sign up to set email alerts
|

Greater Volume of Acute Normovolemic Hemodilution May Aid in Reducing Blood Transfusions After Cardiac Surgery

Abstract: Background Perioperative red blood cell transfusions (RBC) are associated with increased morbidity and mortality after cardiac surgery. Acute normovolemic hemodilution (ANH) is recommended to reduce perioperative transfusions; however, supporting data are limited and conflicting. We describe the relationship between ANH and RBC transfusions after cardiac surgery using a multi-center registry. Methods We analyzed 13,534 patients undergoing cardiac surgery between 2010 and 2014 at any of the 26 hospitals parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 17 publications
3
64
1
11
Order By: Relevance
“…It has been widely used in postpartum hemorrhage, and cancer and orthopedic surgeries, such as joint replacement and spine surgery. These surgeries often have large traumatic areas and a large amount of bleeding, and patients often need blood transfusions (24 -26). ANH advantages include the following.…”
Section: Acute Normovolemic Hemodilution Abtmentioning
confidence: 99%
“…It has been widely used in postpartum hemorrhage, and cancer and orthopedic surgeries, such as joint replacement and spine surgery. These surgeries often have large traumatic areas and a large amount of bleeding, and patients often need blood transfusions (24 -26). ANH advantages include the following.…”
Section: Acute Normovolemic Hemodilution Abtmentioning
confidence: 99%
“…Recent guidelines have suggested that fibrinogen levels should be >200 mg/dL for sufficient clot strength. [9] In the present study, we found that ANH significantly attenuated the decline in fibrinogen, and significantly more patients in ANH group had a fibrinogen level of >200 mg/dL; however, the mean volume of chest tube drainage during the first 24 hours were similar between the groups. This may indicate that both groups had similar amount of bleeding.…”
Section: Discussionmentioning
confidence: 64%
“…[8] However, a recent clinical trial reported a reduced need for transfusion in parallel with the amount of the collected whole blood. [9] Low levels of fibrinogen may increase the need for red blood cell (RBC) transfusion. [10] In this study, we hypothesized that ANH may preserve postoperative plasma levels of fibrinogen and reduce the need for allogeneic blood cell transfusion.…”
mentioning
confidence: 99%
“…In 2015, Goldberg et al . published a multicentre prospective observational study including 13 534 patients undergoing cardiac surgery (Goldberg et al, ). ANH patients were divided into three groups: those who had less than 400 mL removed, those who had 400 to 799 mL removed and those who had 800 mL or greater removed.…”
Section: Resultsmentioning
confidence: 99%